2010
DOI: 10.1021/es101716h
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate Exposure Affects Amino Acids, Mineral Nutrient Status and Antioxidants in Rice (Oryza sativa L.) Genotypes

Abstract: Simulated pot experiments were conducted on four rice (Oryza sativa L.) genotypes (Triguna, IR-36, PNR-519, and IET-4786) to examine the effects of As(V) on amino acids and mineral nutrient status in grain along with antioxidant response to arsenic exposure. Rice genotypes responded differentially to As(V) exposure in terms of amino acids and antioxidant profiles. Total amino acid content in grains of all rice genotypes was positively correlated with arsenic accumulation. While, most of the essential amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 31 publications
7
40
0
3
Order By: Relevance
“…This could be due to inter-varietal difference of Fe accumulation with response to As(III) or As(V) and not due to the pretreatments. Similar inter-varietal difference in Fe content has been earlier reported in different rice cultivars (Dwivedi et al 2010). The translocation of both Mn and Zn increased with As(V) treatments in both the cultivars, however, in the tolerant cultivar pretreating plants with H 2 O 2 and H 2 O 2 +SA, the translocation of both the elements decreased in plants with AsV(4) exposure, on the contrary it increased with As(III) exposure.…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to inter-varietal difference of Fe accumulation with response to As(III) or As(V) and not due to the pretreatments. Similar inter-varietal difference in Fe content has been earlier reported in different rice cultivars (Dwivedi et al 2010). The translocation of both Mn and Zn increased with As(V) treatments in both the cultivars, however, in the tolerant cultivar pretreating plants with H 2 O 2 and H 2 O 2 +SA, the translocation of both the elements decreased in plants with AsV(4) exposure, on the contrary it increased with As(III) exposure.…”
Section: Discussionsupporting
confidence: 86%
“…In the recent years yield loss due As toxicity has been recognized as a serious problem affecting the sustainability of food production in South-East Asian countries89. Triguna, a high yielding rice variety of West Bengal, India was chosen for the present study as it is more tolerant to As among other popular varieties37. The accumulation, transformation and thiol complexation of various As species, commonly present in soil and water, was analyzed to unravel mechanism of As metabolism in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The Os07g0258400 and Os07g0257200 genes ( OsNRAMP1 , OsNRAMP5 ) were more down-regulated (3.1 and 2.9 fold) in the AsIII + SNP treatment as compared to the AsIII treatment (1.49 and 2.1 fold) on 4 th day. The previous study indicated that As accumulation also reduced the iron uptake 29 . OsNRAMP and OsPEZ play a key role in uptake and translocation of As, Fe and Cd 3033 .…”
Section: Resultsmentioning
confidence: 90%
“…Nitrogen and hormone metabolism, as a regulator of plant growth and development, is modulated by heavy metal toxicity and is tightly linked with amino acid and protein metabolism 29, 38 . We, therefore, focused on the analysis of genes involved in amino acid and nitrogen metabolism (Fig.…”
Section: Resultsmentioning
confidence: 99%